In vitro Anthelmintic effect of Melia azedarach L. and Triclinia claussenii C. against sheep gastrointestinal nematodes - Cala, A. C. (2012)
The control of parasitic diseases in small ruminants is mainly done with the use of synthetic anthelmintics. However, incorrect and indiscriminate use of these products has caused the emergence of parasite resistance. Plants with anthelmintic activity are used in folk veterinary medicine, but it is necessary to investigate and scientifically validate low-cost phytotherapeutic alternatives for future use to control gastrointestinal nematodes in small ruminants by family farmers. Thus, the aim of this study was to evaluate the in vitro anthelmintic effect of plant extracts from Melia azedarach and Trichilia claussenii by the egg hatch test (EHT) and larval development test (LDT) against sheep gastrointestinal nematodes. The hexane extract of M. azedarach fruits was extracted through cold percolation and the methanol extract of T. claussenii leaves was obtained by extraction at room temperature in solvents in order of increasing polarity. The efficacy results were analyzed using the Probit program of SAS. The M. azedarach extract showed a LC50 of 572.2 mu g/mL and LC99 of 1137.8 mu g/mL in the EHT, and LC50 of 0.7 mu g/mL and LC99 of 60.81 mu g/mL in the LDT. In turn, the T. claussenii extract presented a LC50 of 263.8 mu g/mL and LC99 of 522.5 mu g/mL in the EHTand LC50 of 1.11 mu g/mL and LC99 of 26.4 mu g/mL in the LDT. Comparing the extracts of the species from the Meliaceae family, T. claussenii showed greater anti-parasite potential in vitro than M. azedarach. However, studies on the isolated compounds, toxicity and administration forms to animals are also needed to validate low-cost alternative herbal remedies for use to control gastrointestinal nematodes by family farmers. (C) 2011 Elsevier B.V. All rights reserved.